2021
DOI: 10.3390/diagnostics11101926
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Non-Invasive Imaging for Detection of Colonic Inflammation in Patients with Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Abstract: Endoscopy is the gold standard for objective assessment of colonic disease activity in inflammatory bowel disease (IBD). Non-invasive colonic imaging using bowel ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI) may have a role in quantifying colonic disease activity. We reviewed the diagnostic accuracy of these modalities for assessment of endoscopically or histopathologically defined colonic disease activity in IBD. We searched Embase, MEDLINE, and the Web of Science from incept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
(96 reference statements)
0
7
0
1
Order By: Relevance
“…However, once disease location and phenotype are established, in many patients, there is an equipoise between MRE and small bowel ultrasound in subsequent disease follow-up and monitoring. SBUS has been shown to be equally accurate for evaluating enteric disease,18–23 cheaper, quicker, better tolerated and, most importantly, preferred by patients 10 24–27. Despite this, US is not widely implemented for CD in the UK, for reasons we do not fully understand.…”
Section: Discussionmentioning
confidence: 99%
“…However, once disease location and phenotype are established, in many patients, there is an equipoise between MRE and small bowel ultrasound in subsequent disease follow-up and monitoring. SBUS has been shown to be equally accurate for evaluating enteric disease,18–23 cheaper, quicker, better tolerated and, most importantly, preferred by patients 10 24–27. Despite this, US is not widely implemented for CD in the UK, for reasons we do not fully understand.…”
Section: Discussionmentioning
confidence: 99%
“…For IBD, FC with a cutoff of 50 µg/g presented the highest sensitivity of 0.92 (0.90-0.94) (42), and MRE showed the highest specificity of 0.93 (0.90-0.95) (30). Besides, other radiological examinations [US, leukocyte scintigraphy (LS), and CT] all performed well with balanced sensitivity and specificity (6,30,43,56,59). However, other biomarkers (CRP and FL) were not as good as radiological examinations (27).…”
Section: Mixed Populationmentioning
confidence: 98%
“…A recent meta-analysis reported that the specificity of US and MRI diagnostic modalities to predict active disease in patients with established or suspected IBD was excellent (91%) when using colonoscopy as the gold standard 26. This indicates there is great ability for these non-invasive tools to distinguish disease-active from disease-free patients.…”
Section: Large Bowelmentioning
confidence: 99%